2015
DOI: 10.1093/jnci/djv063
|View full text |Cite
|
Sign up to set email alerts
|

miR-Test: A Blood Test for Lung Cancer Early Detection

Abstract: Lung cancer is the leading cause of cancer death worldwide. Low-dose computed tomography screening (LDCT) was recently shown to anticipate the time of diagnosis, thus reducing lung cancer mortality. However, concerns persist about the feasibility and costs of large-scale LDCT programs. Such concerns may be addressed by clearly defining the target "high-risk" population that needs to be screened by LDCT. We recently identified a serum microRNA signature (the miR-Test) that could identify the optimal target popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
189
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(193 citation statements)
references
References 24 publications
1
189
2
1
Order By: Relevance
“…However, a high rate of false positive results associated with LDCT screening opened a debate over the cost-effectiveness of LDCT screening programs and the potential harms related to overdiagnosis and radiation-induced cancers. In view of personalised medicine, the potential role for specific, miRNAbased biomarkers to complement the radiological modalities and increase the total sensitivity and specificity of the lung cancer screening process is currently being investigated [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, a high rate of false positive results associated with LDCT screening opened a debate over the cost-effectiveness of LDCT screening programs and the potential harms related to overdiagnosis and radiation-induced cancers. In view of personalised medicine, the potential role for specific, miRNAbased biomarkers to complement the radiological modalities and increase the total sensitivity and specificity of the lung cancer screening process is currently being investigated [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][50][51][52][53][54][55] Reliable quantification of mRNA and microRNA levels for diagnostic and prognostic purposes requires optimal RNA quality and quantity. However, the different instances along the RNA and miRNA analysis workflow can lead to length, sequence, and structure-specific biases in the final expression analysis of a given set of small RNAs.…”
Section: Challenges Faced By the Main Technologies In Nucleic Acmentioning
confidence: 99%
“…Equipment and analysis costs, throughput, and normalization 6,7 still represent obstacles for large-scale nucleic acid biomarker validation [8][9][10][11][12][13][14] and adoption in the clinics [15][16][17] Differences in the nucleic acid purification method, detection technology, and laboratory protocol often lead to different profiling results. Consequently, interpretation of differential expression data and comparisons across different studies has to be done with a note of caution, as standard deviations can span several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the major challenges for lung cancer lies in early precision diagnosis. Currently, routine clinical diagnostic methods includes tumor markers detection, computed tomography screening, histopathological detection and so on which are basically from the point of serology, imaging and pathology [9] and the optimal means of diagnosis are uncertain and lack of data of precision medicine owing to the involvement of different tumors, patient and health-care factors, often in combination [10]. Numerous genetic alterations associated with lung cancer have been identified that might contribute to the development of specific types of lung cancer, patterns of metastasis, drug resistance, or disease recurrence [11].…”
Section: Introductionmentioning
confidence: 99%